The impact of large-scale agricultural investments in low-income economies - Aragie, Emerta A. (SAGE Publications, 2024)
Recent years have witnessed an increasing interest in large-scale agricultural land acquisitions in developing countries. The accompanying socio-economic implications have been areas of debate among politicians, policymakers and development agents. This paper argues that the traditional way of simulating the impacts of these investments in developing countries is misleading as the approach implies that the new investments are identical to the semi-subsistence way of farming that dominates agricultural practices in the host countries. In this study, we incorporate the peculiarity of large-scale agro-investments into an existing database for economy-wide models, i.e., social accounting matrix (SAM), and capture welfare and distributional outcomes properly. SAM-based multiplier models applied to Ethiopian data justify the need to account for the peculiarity of the investments in terms of production technology and their geographic distribution.